2004
DOI: 10.1002/jmv.20125
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to hepatitis E virus among Japanese blood donors: Identification of three blood donors infected with a genotype 3 hepatitis E virus

Abstract: Risk factors for acquiring hepatitis E among individuals in industrialized countries including Japan are not fully understood. We investigated whether Japanese blood donors with or without an elevated alanine aminotransferase (ALT) level are likely to have hepatitis E virus (HEV) infection. Serum samples were collected from 5,343 voluntary blood donors including 1,087 donors with elevated ALT of 61-966 IU/L and 4,256 donors with normal ALT (< or = 60 IU/L) at two Japanese Red Cross Blood Centers, and were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 50 publications
2
50
1
1
Order By: Relevance
“…This is the first report that investigated the prevalence of HEV antibody in hemophilia patients in Japan. The prevalence of HEV antibody in our study patients (16.3%) was higher than that previously reported in Japanese blood donors (3.7%) [29] and in Japanese patients undergoing hemodialysis (9.4%) [20] ( table 4 ). The gradual increase in the prevalence of HEV antibody between healthy blood donors, patients undergoing hemodialysis, and patients with hemophilia suggests a possible role of parenteral transmission of HEV.…”
Section: Discussioncontrasting
confidence: 54%
“…This is the first report that investigated the prevalence of HEV antibody in hemophilia patients in Japan. The prevalence of HEV antibody in our study patients (16.3%) was higher than that previously reported in Japanese blood donors (3.7%) [29] and in Japanese patients undergoing hemodialysis (9.4%) [20] ( table 4 ). The gradual increase in the prevalence of HEV antibody between healthy blood donors, patients undergoing hemodialysis, and patients with hemophilia suggests a possible role of parenteral transmission of HEV.…”
Section: Discussioncontrasting
confidence: 54%
“…The sero-prevalence of the infection in developing countries with poor sanitation as well as in developed countries has been reported to be respectively higher and lower than Iran (17)(18)(19). Abe et al (2006) reported that the sero-prevalence of hepatitis E in Europe, Brazil, Japan, China, and the Middle East is respectively 0.95% -20.6%, 2.3%, 3.7%, 32.6%, and 4% -5.2% (20).…”
Section: Discussionmentioning
confidence: 99%
“…HEV is not only a problem in developing countries but has also become a concern of developed countries (Christensen et al, 2002;Clemente-Casares et al, 2003;Fukuda et al, 2004). The high seroprevalence despite the rarity of disease morbidity in the developed countries is still unexplained .…”
Section: Discussionmentioning
confidence: 99%